Proceedings of the IEEE 1999 Custom Integrated Circuits Conference (Cat. No.99CH36327)
DOI: 10.1109/cicc.1999.777334
|View full text |Cite
|
Sign up to set email alerts
|

A 5 GHz, 1 mW CMOS voltage controlled differential injection locked frequency divider

Abstract: A voltage controlled differential injection locked frequency divider (VCDILFD) with a large locking range is designed in a 0.24p.m CMOS technology. A 29% locking range is achieved by an optimal inductor design and also by employing high Q accumulation mode MOS varactors t o change the freerunning oscillation frequency of the divider. The measurement results show frequency division at 5GHz with more than l G H z locking range and power consumption of less than 1mW.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The core of the VCILFD is based on the approach originally proposed in [13,14] and incorporates high-frequency SiGe BJT instead of MOSFET devices. The injected signal is applied to the base of Q 1 and then delivered to the common emitter connection of Q 2 and Q 3 .…”
Section: Circuit Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The core of the VCILFD is based on the approach originally proposed in [13,14] and incorporates high-frequency SiGe BJT instead of MOSFET devices. The injected signal is applied to the base of Q 1 and then delivered to the common emitter connection of Q 2 and Q 3 .…”
Section: Circuit Descriptionmentioning
confidence: 99%
“…Several methods are proposed for injection-locked frequency division operating at gigahertz frequencies [8][9][10][11][12][13][14]. In this work, we present multiband design solutions for frequency division by employing injection locking.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 2, the output nodes Iϩ and IϪ are direct coupled to the gates of Mc3 and Mc4, and the output nodes Qϩ and QϪ are crosscoupled to the gates of Mc2 and Mc1, respectively. It has been shown that both differential VCOs will synchronize to a single oscillation frequency at steady state and quadrature outputs Iϩ, IϪ, Qϩ, QϪ can be generated [7]. The resistances Rs are used to bias the gates of the coupling transistors Mc1-Mc4 and let the gate to source voltages (V gs ) are the same.…”
Section: Circuit Designmentioning
confidence: 99%
“…The literature reports widespread values of divideby-two locking ranges, e.g., from 12% in [6] to 29% in [7], both of which have been obtained for similar frequencies of oscillation, power supply voltages, power consumptions, and by using very similar ILFD topologies. Such different locking ranges for very similar circuits reveals that: I) the locking range of ILFDs is not necessarily small; II) there is a need for methods to optimize the locking range of ILFDs with respect to their design parameters.…”
Section: Introductionmentioning
confidence: 97%